Avaliação do Gasto Energético em Indivíduos com Síndrome Pós- Poliomielite (SPP): Através do Questionário de Atividade Física Habitual de Baecke - Pereira, Roberto Dias Batista [UNIFESP] (2009)
The Post-Polio Syndrome (PPS) is a late effect of polio, being classified as motor neuropathy, because of the clinical and histological features are closely related to dysfunction of lower motor neurons. New symptoms or worsening of residual symptoms, especially the new weakness, muscle fatigue, new atrophy, muscle pain, joint pain and intolerance to cold, develop 30 to 50 years after acute poliomyelitis. The causes of these new symptoms remain unknown, however, seem to be related to a dysfunction of the motor unit by axonal damage and peripheral neuromuscular junction. Among the various causes, the most accepted is the "overuse" (overload or supertraining). There is no consensus on the implementation of physical activity or inactivity on the appearance of new symptoms. Therefore, this work will contribute to the knowledge of the profile of energy expenditure in individuals with a history of prior paralytic polio, presenting or not symptoms of PPS, and assessed the history of their Habitual Physical Activity (HPA) for the Baecke questionnaire. Of the 410 patients enrolled in the Sector of Investigation of Neuromuscular Diseases, UNIFESP / EPM, 28 patients with poliomyelitis sequelae (PS), 52 with PPS and other 36 individuals as part of the control group (CG), totaling 116 individuals assessed, were selected for this study. Patients with PPS in their history had tended to increase their HPA between 10 to 20 years of age (AV1), compared to the sequelae of polio and the control group. Already in the period of 21 to 30 years (AV2) there was a significant increase in their Occupational Physical Activity (OPA) in relation to the PS group (PS=2500 and PPS=3000, Kruskal-Wallis test, p <0.035), and the OPA-AV2 showed correlation with age of onset of PPS (Pearson, r = - 0.2796, p <0.0447). Increased presence of fatigue (PPS=92.3%, PS=42.9% and CG=7% - Kruskal- Wallis test, p <0.0001), lower quality of life (physical and psychological domains, Anova Test , p <0.0001; Environment domain, Kruskal-Wallis test, p = 0.0312) and lowest total score (TS) of HPA (TS: PPS=9625; PS=11130 and CG= 11000, test of Kruskal-Wallis , p <0.0001) of the PPS group for the other, shows their current state of the disease. It was noted that the presence or absence of fatigue did not influence the appearance of the PPS. There was increase in Body Mass Índex (BMI) in the population with PPS and PS in the categories of appropriate and overweight (p=0.0165, chi-square test), which is an aggravating factor for them. This work concluded that patients with PPS have a nosological entity with its own characteristics, such as: history of higher energy expenditure during the life, especially in occupational physical activity, from 21 to 30 years of age, suggesting that the critical decade for the development of this disease; presence of the differential current clinical status in relation to polio sequelae (PS) and Control (CG) groups, with a higher frequency of fatigue, lower scores on HPA and, consequently, a poorer quality of life; increased tendency to overweight, which can be an aggravating factor for the development or intensification of these limitations, but it is not possible to identify whether it was the high BMI that decreased physical capacity for HPA, or if was the current clinical state that promoted an increase in BMI; the later the acute polio, worse functional recovery, lower potential for engagement in physical activities more intensive, higher risk of developing PPS. The development of SPP more frequent in patients with acute polio later indicates that the surviving motor unit reinnervation process presents (plasticity) more unstable, more vulnerable to processes that lead to aging or cellular or a degenerative process.